Methyltransferase as Antibiotics Against Foodborne Pathogens: An In Silico Approach for Exploring Enzyme as Enzymobiotics - Ahmad, Varish; Ahmad, Aftab; Abuzinadah, Mohammed F.; Al-Thawdi, Salwa; Yunus, Ghazala (Frontiers in Genetics, 2022)
The development of resistance in microbes against antibiotics and limited choice for the use of chemical preservatives in food is the urgent need to search an alternative to antibiotics. The enzymes are catalytic protein that catalyzes digestion of bacterial cell wall as well as protein requirements for the survival of the cell. In this study, the methyltransferase enzyme sequence modeled and its interaction was tested against a membrane protein of the gram-positive and gram-negative bacteria through in-silico protein-protein interactions. The methyltransferase interaction with cellular protein was found to be maximum, due to the maximum PatchDock Score(15808) which was followed by collicin (12864) and amoxicillin (4122). The modeled protein has found to be interacted more significantly to inhibit the pathogen bacteria than the tested antibiotics and antimicrobial colicin protein. Thus, modeled enzyme methyltransferase sequence could be used as enzymobiotics. Thus, the peptide sequences similar to this enzyme need to be design, synthesize and evaluate against the microbial pathogen.